2022
DOI: 10.1038/s41467-021-27885-2
|View full text |Cite
|
Sign up to set email alerts
|

Selectively tuning ionic thermopower in all-solid-state flexible polymer composites for thermal sensing

Abstract: There has been increasing interest in the emerging ionic thermoelectric materials with huge ionic thermopower. However, it’s challenging to selectively tune the thermopower of all-solid-state polymer materials because the transportation of ions in all-solid-state polymers is much more complex than those of liquid-dominated gels. Herein, this work provides all-solid-state polymer materials with a wide tunable thermopower range (+20~−6 mV K−1), which is different from previously reported gels. Moreover, the mech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 64 publications
3
55
1
Order By: Relevance
“…By applying a temperature gradient (Δ T ) through an ionic polymer film, the thermodiffusion of ionic carriers from hot to cold parts generates a voltage due to the Soret effect. 3–7 To identify the major ion carrier in the LCI film, time-of-flight secondary ion mass spectrometry (ToF-SIMS) was carried out for surface analysis in negative ion mode (Fig. S13, ESI†), and samples for both ends near the electrode were prepared by applying Δ T = 8.2 K at 80 °C and 80% RH followed by drying.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By applying a temperature gradient (Δ T ) through an ionic polymer film, the thermodiffusion of ionic carriers from hot to cold parts generates a voltage due to the Soret effect. 3–7 To identify the major ion carrier in the LCI film, time-of-flight secondary ion mass spectrometry (ToF-SIMS) was carried out for surface analysis in negative ion mode (Fig. S13, ESI†), and samples for both ends near the electrode were prepared by applying Δ T = 8.2 K at 80 °C and 80% RH followed by drying.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Among the possible power sources for intelligent devices, ionic thermoelectrics (iTEs) composed of ionic polymers are emerging as competitive candidates in terms of a high thermovoltage generation compared to traditional organic thermoelectrics due to their potential as soft wearable electronics and Seebeck voltages that are large enough to operate low-voltage driving electronics from a small thermal gradient between the environment and iTEs. 3–11 The thermoelectric performance of materials is defined using the thermoelectric figure of merit, , where S is the Seebeck coefficient, σ is the carrier conductivity, T is the absolute temperature, and κ is the thermal conductivity. 12 Generally, the electric thermoelectric performance of polymers depends on the power factor (PF = S 2 σ ) due to their intrinsically low thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…With the same polymer as a gel and ionic liquid Na:TFSI as an energy carrier, Chi and his co-workers reported a change in S i from 20 to −6 mV K −1 (namely from the p-type to n-type) by adding TPFPB into the gel, which effectively traps the migration of Na + cations. 107 In another interesting investigation, Liu et al reported a giant and bidirectionally tunable S i value in non-aqueous ionogels by ion doping. 42 In his work, the same S i value (−4 mV K −1 , n-type) is reported in the EMIM:TFSI/PVDF-HFP ionogel due to the anion dominated thermodiffusion.…”
Section: Engineering Designs For Thermo-electrochemical Cellsmentioning
confidence: 99%
“…Recently, researchers have widely utilized TCCs in thermal sensing based on their giant thermopower. 106,107 As shown in Fig. 10E, a thermal sensor is successfully developed for early fire alarming.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
See 1 more Smart Citation